Investigation of the efficacy of identified acetolactate synthase inhibitors, peptidyl cysteine protease inhibitors, thiolactomycins, and thiosemicarbazone compounds against Mycobacterium tuberculosis - Sebesho, Biopelo Felicity (Division of Immunology, 2014)
Includes bibliographical references (leaves 131-141).